2017
DOI: 10.1371/journal.pone.0176537
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of immunogenicity and protective efficacy of recombinant outer membrane proteins of Haemophilus parasuis serovar 5 in a murine model

Abstract: Glässer’s disease is an economically important infectious disease of pigs caused by Haemophilus parasuis. Few vaccines are currently available that could provide effective cross-protection against various serovars of H. parasuis. In this study, five OMPs (OppA, TolC, HxuC, LppC, and HAPS_0926) identified by bioinformatic approaches, were cloned and expressed as recombinant proteins. Antigenicity of the purified proteins was verified through Western blotting, and primary screening for protective potential was e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…parasuis vaccine development has suffered from difficulty generating a broadly cross-protective vaccine. Many platforms have been attempted: whole cell bacterins, outer-membrane vesicles, live avirulent strains, and a variety of subunit vaccines [5,6,13,15,[24][25][26][27]. While homologous protection with whole cell vaccines is often high, those studies investigating heterologous protection show less efficacy [7][8][9][10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…parasuis vaccine development has suffered from difficulty generating a broadly cross-protective vaccine. Many platforms have been attempted: whole cell bacterins, outer-membrane vesicles, live avirulent strains, and a variety of subunit vaccines [5,6,13,15,[24][25][26][27]. While homologous protection with whole cell vaccines is often high, those studies investigating heterologous protection show less efficacy [7][8][9][10].…”
Section: Discussionmentioning
confidence: 99%
“…Several mechanisms have been employed to identify subunit vaccine candidates, including the use of hyperimmune or post-challenge serum from pigs to identify proteins separated by gel electrophoresis and in silico prediction methods [13][14][15]. In this report, we utilized a previously reported functional genomic screen to identify subunit vaccine candidates [16].…”
Section: Introductionmentioning
confidence: 99%
“…Most Clinical studies had shown that the protection of inactivated vaccine was mainly against isolates of the same serovars, and its cross-protection was extremely limited (10), for this reason, choosing inactivated vaccines of local epidemic serotypes was more bene cial to defend against H. parasuis. In different regions and a combination of protective antigens might be able to provide effective protection against multiple H. parasuis serovars (23).…”
Section: Discussionmentioning
confidence: 99%
“…14/220) are successively reduced. In 2017, Guangdong Province accounted for the highest separation rate(16.11%, 168/1043), followed by Shandong Province (12.5%,23/184) and Hunan Province (12.03%, 35/291), then the separation rate of Guangxi Province (11.88%, 12/101), Hubei Province (8.8%, 161/1829), Henan Province (8.58%, 79/921), Sichuan Province (7.41%, 16/216), Fujian Province (6.06, 12/198), Anhui Province (5.04%, 7/139), Shaanxi Province (4.23%, 3/71), Jiangsu Province (4.1%, 5/122) and Shanxi Province (3.92%, 2/51) decreased in turn. In 2018, Zhejiang Province accounted for the highest separation rate (20.34%, 12/59), followed by Guangdong Province (13.11%, 110/839), Besides, the separation rate of Fujian Province (10.98%, 19/173), Guangxi Province (9.02%, 12/133), Henan Province (7.58%, 75/990), Hunan Province (7.14%, 12/168), Hubei Province (5.41%, 91/1682) and Shandong Province (5.17%, 6/116) decreased in turn.…”
mentioning
confidence: 99%
“…The upregulated gene tolC found in this study encodes an Omp (TolC) lipoprotein that forms a trimeric channel and acts in the transport of several molecules [ 32 ]. Li et al [ 33 ] observed that mice immunized with this protein and then challenged with H. ( G. ) parasuis showed a survival rate of 80%.…”
Section: Discussionmentioning
confidence: 99%